Values of Individualization in Science & Social Studies Textbooks - Vasilijević, Danijela N.; Đurović, Ljiljana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Ways of achieving individualization of the learning process are one of the most important issues of modern didactics. They represent a new approach to creating modern systems of teaching. There is a growing discussion about developmental teaching that can be characterized as a model of individualized teaching. This is the answer to the classical organization of teaching in a class-lecture system in which teaching content, teaching methods, learning styles and all other working conditions are the same for all students. Therefore, the creation of a modern Science & Social Studies textbook which should meet the requirements of modern teaching has a great social importance and requires joint efforts of theoreticians, researchers and practitioners. When the textbooks is well-designed, we can expect improved student activity in didactic and methodological sense, development of his individuality and creativity, as well as positive influence on his self-formation and self-actualization. Starting from the notion of individualization, the textbook as an assumed scenario of the learning and teaching process, the authors determine the goal of the research: to examine the presence of values of individualization in Science & Social Studies textbooks for the fourth grade of primary school. The research sample is deliberate and stratified: it consists of Science & Social Studies textbooks for the fourth grade of primary school, published by the Institute for Textbooks Publishing and Teaching Aids. 121 primary school teachers from the Zlatibor and Moravicki Districts participated in this research. Independent evaluators assessed the distribution of several categories that relate to the values of individualization: 1) content in two levels of difficulty – remedial content for students with poor performance and additional content for good students; 2) examples designed in three levels of difficulty – for students with the weakest performance, for average students and for exceptional students; 3) exercises in three levels of difficulty - for students with the weakest performance, for average students and for exceptional students; 4) various procedures for solving problem-based tasks where: there are several problem-based tasks and students need to choose one, students just need to solve problem-based tasks, students define and solve problem-based tasks on their own and students identify the problem, formulate and solve it. The Likert five-point scale of responses was used for the evaluation of primary school teachers’ attitudes toward the present values of individualization in the sample textbooks. The data was processed with the use of SPSS 16.0 software package, and the hypotheses were tested by calculating the intelligence quotient and the chi square. The results of the evaluation of primary school teachers by independent evaluators show that the values of individualization are insufficiently present in Science & Social Studies textbooks, that teachers’ qualifications and years of experience do not affect the results and that this problem needs a more significant scientific research and professional attention. The issue of modernizing existing Science & Social Studies textbooks is thus actualized. One of the possible solutions could be an electronic Science & Social Studies textbook which can offer better technical solutions than its classic equivalent and help individualize educational work.